An exploration of knowledge, attitudes and behaviours of young multiethnic Muslim-majority society in Malaysia in relation to reproductive and premarital sexual practices - Li Ping Wong (2012)
The increasing trend of premarital sexual experience and unintended pregnancies in Malaysia warrants sustained and serious attention. The sensitivities of sex-related issues in a Muslim-majority country create various types of barriers to sexual and reproductive health information, support and practices. This study aims to gain understanding of knowledge, attitudes and behaviours of young women in Malaysia concerning reproductive, contraception and premarital sexual practices. A cross-sectional study was performed, using an anonymous self-administered questionnaire carried out among 1695 female university students in a public university in Malaysia. Respondents had low scores for knowledge of reproduction and pregnancy (median=4, of maximum score 10), contraceptive uses (median=6, of maximum score 16) and contraceptive availability (median=3, of maximum score 13). The majority of women surveyed do not have liberal values in relation to premarital sexual behaviour (median=37, of maximum 40); higher scores on this scale corresponded to opposing premarital sex. The multivariate analyses showed that ethnic group was the strongest correlate of knowledge and attitude scores; being of Malay Muslim ethnicity was associated significantly with lower knowledge scores and premarital sex permissiveness. Other significant correlates were year of study, maternal occupational groups, level of religious faith, dating status and urban–rural localities. Level of premarital sex permissiveness was inversely correlated with reproduction and pregnancy knowledge score, and contraceptive knowledge scores. Reproductive health knowledge and attitudes were intricately linked to religious values and cultural norms differences surrounding sexual issues.